Adoption of Telehealth: Remote Biometric Monitoring among Peritoneal Dialysis Patients in the United States. Issue 5 (September 2017) - Lew, Susie Q.; Sikka, Neal; Thompson, Clinton; Cherian, Teena; Magnus, Manya
We examined participant uptake and utilization of remote monitoring devices, and the relationship between remote biometric monitoring (RBM) of weight (Wt) and blood pressure (BP) with self-monitoring requirements. Participants on peritoneal dialysis (PD) (n = 269) participated in a Telehealth pilot study of which 253 used remote monitoring of BP and 255 for Wt. Blood pressure and Wt readings were transmitted in real time to a Telehealth call center, which were then forwarded to the PD nurses for real-time review. Uptake of RBM was substantial, with 89.7% accepting RBM, generating 74, 266 BP and 52, 880 Wt measurements over the study period. We found no significant correlates of RBM uptake with regard to gender, marital, educational, socio-economic or employment status, or baseline experience with computers; frequency of use of BP RBM by Black participants was less than non-Black participants, as was Wt RBM, and participants over 55 years old were more likely to use the Wt RBM than their younger counterparts. Having any review of the breach by a nurse was associated with reduced odds of a subsequent BP breach after adjusting for sex, age, and race. Remote biometric monitoring was associated with adherence to self-monitoring BP and Wt requirements associated with PD. Remote biometric monitoring was feasible, allowing for increased communication between patient and PD clinical staff with real-time patient data for providers to act on to potentially improve adherence and outcomes.